A Social Analgesic? Acetaminophen (Paracetamol) Reduces Positive Empathy - Mischkowski, Dominik; Crocker, Jennifer; Way, Baldwin M. (Frontiers in Psychology, 2019)
Acetaminophen – a potent physical painkiller that also reduces psychological reactivity, including empathy for other people’s pain – blunts physical and social pain by reducing activation in brain areas thought to be related to emotional awareness and motivation, such as the anterior insula and anterior parts of the cingulate cortex. Some neuroimaging research on positive empathy (i.e., the perception and sharing of positive affect in other people), suggests that the experience of positive empathy also recruits these paralimbic cortical brain areas. We thus hypothesized that acetaminophen may also impair affective processes related to the experience of positive empathy. We tested this hypothesis in a double-blind randomized-controlled experiment. Specifically, we administered 1000 mg acetaminophen or a placebo and measured effects on different measures of positive empathy while participants read scenarios about the uplifting experiences of other people. Results showed that acetaminophen reduced personal pleasure and other-directed empathic feelings in response to these scenarios. In contrast, effects on perceived positivity of the described experiences or perceived pleasure in scenario protagonists, were not significant. These findings suggest that (a) acetaminophen reduces affective reactivity to other people’s positive experiences, and (b) the experience of physical pain and positive empathy may have a more similar neurochemical basis than previously assumed. Because the experience of positive empathy is related to prosocial behavior, our findings also raise questions about the societal impact of excessive acetaminophen consumption.